PENGELOLAAN DAN PENDAYAGUNAAN DANA ZAKAT, INFAK, SEDEKAH PADA MASA PANDEMI COVID-19 DI BAZNAS KOTA TANGERANG DALAM PERSPEKTIF FATWA MUI NOMOR 23 TAHUN 2020 - Nur Jamaludin; Viona Hanatasya; Muklis Muklis (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2022)
This study aims to determine the governance and Utilization of Zakat, Infaq, Alms Funds at the Tangerang City Baznas in the Perspective of MUI Fatwa Number 23 of 2020. This study uses qualitative methods to describe the utilization of zakat, infaq, and alms (ZIS) funds. The source of this research data was taken through interviews with the daily chief executive and staff from the Tangerang City BAZNAS distribution division as core informants and also supporting informants such as mustahik who received program assistance after the MUI fatwa Number 23 of 2020. Other data were taken from various related documentation and articles. with this research. The results of this study explain that the management of ZIS funds at BAZNAS Tangerang City has been running according to the rules because it always refers to the annual budget work plan based on RELU (Distribution Realization) and RESTRA (Strategic Plan) for the next 5 years and is prepared according to the annual budget work plan. In addition, Tangerang City BAZNAS has carried out optimal management of zakat funds in accordance with MUI Fatwa Number 23 of 2020.